Synthesis of 2-[(Bis-(2-chloroethyl)amino)acetamido]-5-substituted-1,3,4-thiadiazole as Possible Alkylating Anticancer Agents - Gowramma, B.; Murugan, V.; Sumathi, K.; Kumar, E.P.; Suresh, B.; Reddy, V.M. (Asian Journal of Chemistry, 2010)
A few series of 2-[(bis-(2-chloroethyl)amino)acetamido]-5-substituted-1,3,4-thiadiazole have been synthesized by chlorination of 2-[(bis-(2-hydroxyethyl)amino)acetamido]-5-substituted- 1,3,4-thiadiazole with phosphorous oxychloride and phosphorous pentachloride. The synthesized compounds containing nitrogen mustards were screened for their anticancerous activity by short term in vitro and in vivo anticancer activity by body weight analysis, mean survival time and percentage increase in life span method using Swiss albino mice bearing Dalton's Lymphoma ascites (DLA) 1 x 106 cells/mL. The structures of the synthesized compounds were confirmed by spectral analysis (IR, NMR and mass). Investigation of anticancer activity was done by using DLA cell line. Only compound E showed significant activity in the antitumour screening when compared with the control, i.e., mice treated with CMC.